Navigating the Digital Society: Financial Literacy as a Tool for Empowerment - Ade Maharini Adiandari (UIN Sunan Gunung Djati, 2023)
In an era of an increasingly digitalized society, digital financial literacy has become a necessity to equip individuals with the knowledge and skills necessary to manage personal finances and take advantage of investment opportunities in a complex digital economic environment. This research aims to deepen understanding of financial literacy in a digital society and identify existing challenges and opportunities. This research uses a descriptive qualitative approach with data obtained from various research results and previous studies that are relevant to this research. The results of this research identify challenges, such as lack of motivation and complexity of financial products, as well as challenges measuring literacy levels and inequality of access. To achieve more equitable and sustainable financial literacy, fiscal incentives can also be used to encourage community participation in financial literacy programs. With the joint efforts of government, the financial industry, and society, we can achieve a more financially aware and skilled society in this ever-evolving digital era.